Enjoy the Same Liberty: Black Americans and the Revolutionary Era - Countryman, Edward (Rowman & Littlefield Publishers, 2011)
In this cohesive narrative, Edward Countryman explores the American Revolution in the context of the African American experience, asking a question that blacks have raised since the Revolution: What does the revolutionary promise of freedom and democracy mean for African Americans? Countryman, a Bancroft Prize-winning historian, draws on extensive research and primary sources to help him answer this question. He emphasizes the agency of blacks and explores the immense task facing slaves who wanted freedom, as well as looking at the revolutionary nature of abolitionist sentiment. Countryman focuses on how slaves remembered the Revolution and used its rhetoric to help further their cause of freedom. Many contend that it is the American Revolution that defines us as Americans. Edward Countryman gives the reader the chance to explore this notion as it is reflected in the African American experience.